Developing a quick and inexpensive in vitro (non‐animal) bioassay for mascara irritation. (3rd December 2013) - Thomason, H.; Montagnes, D. J. S.
Synopsis Objective Mascara is a mild irritant that causes a range of medical problems. Animal models to predict ocular irritation have, however, been questioned at a number of levels, and there is a continued need to develop in vitro testing methods. Methods We assess changes in an easily quantifiable attribute, ciliated protozoan growth rate, as a sensitive, sublethal measure. Specifically, we test six, randomly chosen, commercial mascara products against a control (as treatments) and reveal through ANOVA (n = 6, α = 0.05) significant differences in the specific growth rate to treatments (for both protozoa). Results We provide evidence that two easily cultured protozoa (Paramecium caudatum, Blepharisma japonicum) should be considered as models to assess ocular irritancy (and possibly cosmetics in general) and establish the groundwork for such studies to be applied at a more commercial level. We do this by developing a bioassay for mascara toxicity and indicate the low cost (after equipment is purchased, on the order of $100s) and the ease of performing such tests (able to be conducted by undergraduate students), as a consideration for their future commercial application. We first examined dose dependence of responses, revealing that there was a need to conduct preliminary work to determine appropriate levels for sublethal responses. We then show that some products resulted in mortality at high concentrations, others decreased growth rate by >50% (compared with the control), whereas others had no significant effect, compared with the control. Conclusion We have provided a novel, quick and inexpensive means to assess mascara; the next step is to validate these ciliate bioassays by comparison with animal testing and epidemiological studies, which is beyond the scope of this fundamental 'proof‐of‐concept' study.